Removal of Endotoxin during Purification of Poly(3-Hydroxybutyrate) from Gram-Negative Bacteria - Lee, Sang Yup (American Society for Microbiology, 1999)
Poly(3-hydroxybutyrate) (PHB) was produced by cultivating several gram-negative bacteria, including Ralstonia eutropha, Alcaligenes latus, and recombinant Escherichia coli. PHB was recovered from these bacteria by two different methods, and the endotoxin levels were determined. When PHB was recovered by the chloroform extraction method, the endotoxin level was less than 10 endotoxin units (EU) per g of PHB irrespective of the bacterial strains employed and the PHB content in the cell. The NaOH digestion method, which was particularly effective for the recovery of PHB from recombinant E. coli, was also examined for endotoxin removal. The endotoxin level present in PHB recovered by 0.2 N NaOH digestion for 1 h at 30°C was higher than 10(4) EU/g of PHB. Increasing the digestion time or NaOH concentration reduced the endotoxin level to less than 1 EU/g of PHB. It was concluded that PHB with a low endotoxin level, which can be used for various biomedical applications, could be produced by chloroform extraction. Furthermore, PHB with a much lower endotoxin level could be produced from recombinant E. coli by simple NaOH digestion.